2013
DOI: 10.1109/tvcg.2012.324
|View full text |Cite
|
Sign up to set email alerts
|

Combining Computational Analyses and Interactive Visualization for Document Exploration and Sensemaking in Jigsaw

Abstract: Investigators across many disciplines and organizations must sift through large collections of text documents to understand and piece together information. Whether they are fighting crime, curing diseases, deciding what car to buy, or researching a new field, inevitably investigators will encounter text documents. Taking a visual analytics approach, we integrate multiple text analysis algorithms with a suite of interactive visualizations to provide a flexible and powerful environment that allows analysts to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 61 publications
0
40
0
2
Order By: Relevance
“…This strategy has been extensively discussed in the visualization community to facilitate investigative analysis [45,53], the exploration of news articles [11], book collections [46], and artworks [21]. Studies have shown that the strategy of coordinated views is useful for the analysis of large and complex document collections, both in professional [5,18] and casual contexts [11,21]. Thudt et al highlight this strategy as particularly effective for supporting open-ended exploration and serendipitous discoveries [46].…”
Section: Related Workmentioning
confidence: 99%
“…This strategy has been extensively discussed in the visualization community to facilitate investigative analysis [45,53], the exploration of news articles [11], book collections [46], and artworks [21]. Studies have shown that the strategy of coordinated views is useful for the analysis of large and complex document collections, both in professional [5,18] and casual contexts [11,21]. Thudt et al highlight this strategy as particularly effective for supporting open-ended exploration and serendipitous discoveries [46].…”
Section: Related Workmentioning
confidence: 99%
“…In addition to specific graphs, more complex applications, such as new/s/leak (Yimam et al, 2016), Jigsaw (Görg et al, 2013) or Overview 2 , have been developed to support document exploration by integrating many different techniques, including graphs, in a single application. In contrast to our work, their focus is on productive use, while we are mainly interested in the experimental evaluation, requiring us to study the use of specific graphs in isolation.…”
Section: Related Workmentioning
confidence: 99%
“…An extensive discussion of academic research projects employing visual analytics for understanding text and document collections can be found in [2]. The scenario exploring the 9/11 Commission Report and the images used in this article were produced using the Jigsaw visual analytics system.…”
Section: Sidebar: Visual Analytics Tools For Intelligence Analysismentioning
confidence: 99%
“…Early versions of Jigsaw emphasized a suite of interactive visualizations portraying the documents' contents and connections between entities in the documents [10]. More recently, we have integrated computational text analysis capabilities [2]. Beyond intelligence analysis, Jigsaw has been used to explore consumer review, academic research, fraud, investigative reporting, law enforcement, business intelligence, and email document collections.…”
Section: Sidebar: Visual Analytics Tools For Intelligence Analysismentioning
confidence: 99%
See 1 more Smart Citation